109 The ABN Acute Neurology Boot Camp: Pre- and post-course feedback for the inaugural event. Issue 6 (27th May 2022) - Rees, Richard N; Shribman, Sam; Jones, Matt; Warner, Thomas T; Sussman, Jon
Abstract : Introduction: The transition from medical SHO to neurology registrar is a period fraught with anxiety and stress. Returning from parental leave or out-of-programme experiences can engender similar feelings in more experienced neurology trainees. We sought to support junior and senior neurology trainees through this period by organising the inaugural ABN Acute Neurology Boot Camp. Methods: The ABN delivered a one-day course covering a range of acute neurology topics. Sessions were delivered by a gender-balanced panel of early-stage consultants who had been recommended by current trainees for their teaching style and enthusiasm. Participants completed a pre- and post-course survey. The primary outcome measure was the self-rated level of confidence in being the neurology registrar on-call using a 10-point Likert scale. Results: 73 trainees attended from across the UK. The median pre-course confidence level was 4 (IQR 3), which improved to median 6 (IQR 2) (p<0.0001). Both junior (FY1-CT2) and senior trainees (ST3+) reported improvement as a result of the course. Confidence in managing acute presentations in each of the topic areas improved significantly. Discussion: Trainees benefit significantly from being supported through these points of transition. The Acute Neurology Boot Camp is a useful and effective method of providing education and support. richard.n.rees@ucl.ac.uk